Impacto da laserterapia de baixa potência em modelo de carcinogênese oral induzido por 4-nitroquinolina-n-óxido (4-NQO) na língua de camundongos - Carmo Filho, José Ronildo Lins do (2023)
Oral squamous cell carcinoma (CEC) is the most common malignant neoplasm of the oral cavity, corresponding to approximately 94% of cases in this region. Low-intensity laser demonstrates basic anti-inflammatory, analgesic and biomodulation effects, but there is no consensus in the literature regarding its role in oral malignant lesions and potentially malignant disorders, as well as in the tumor microenvironment. The objective of this work was to evaluate the influence of low-level laser therapy (LTBI) in a model of oral carcinogenesis induced by 4-nitroquinoline-n-oxide (4-NQO). For this, 96 Swiss mice were subjected to topical application of 1% 4-NQO on the surface of the lingual dorsum, daily, for 20 weeks. The animals were divided into eight groups: a negative control group (GCN) treated with 4-NQO diluent (DMSO), a positive control group (GCP) treated with 1% 4-NQO, and six experimental groups (GT) treated with with 4-NQO 1% and co-treated with LTBI [red laser (LV) and infrared laser (LIV)]: starting at week zero (GT1 with LV and GT4 with LIV), at the twelfth week (GT2 with LV and GT5 with LIV) and in the sixteenth week (GT3 with LV and GT6 with LIV). The animals were euthanized after 20 weeks and the tongues were removed for processing and making histological slides for analysis of the presence and severity of cellular and architectural alterations of the lesions (dysplastic and neoplastic), immunohistochemical reactions (Ciclin D1 and Ki-67), myeloperoxidase (MPO), n-acetyl-β-d-glucosaminidase (n-AG), malondialdehyde (MDA), reduced glutathione (GSH), total proteins, tumor necrosis factor alpha (TNF- α), interleukin 1β (IL-1β) and interleukin 6 (IL-6). For all analyses, the statistical software GraphPad Prism 5.0® was used, with a significance level of p<0.05. The group that received only 4-NQO showed a significant increase in the frequency of carcinoma (p<0.001), an increase in the frequency (%) of positive expression for Cyclin D1 and Ki-67 (p<0.005), in addition to increased levels of TNF-α, IL-1β, IL-6, MPO, n-AG, MDA and total proteins (p<0.001) when compared to GCN; and all groups treated with laser, regardless of whether red or infrared, showed a significant reduction in these parameters. Finally, there was an increase in reduced glutathione levels only in the groups treated with LIV when compared to the 4-NQO group (p<0.001). These results show that low level laser therapy (with red and infrared laser) reduced the development of tumors in a model of oral carcinogenesis induced by 4-NQO in the tongue of mice, and this effect was accompanied by a reduction in the expression of markers associated with tumor proliferation and aggressiveness, reduced influx of inflammatory cells, cytokines associated with mechanisms of inflammation and carcinogenesis (TNF-α, IL-1β, IL-6), in addition to an improvement in tissue redox balance.